THE NUTRIENT DIGESTIBILITY OF KAMPUNG CHICKEN FED RATIONS WITH ISO ENERGY AND DIFFERENT LEVEL PROTEIN - I M. P., Sugiarta; Puger, A. W.; Nuriyasa, I M. (Jurnal Peternakan Tropika, 2018)
This study aims to determine the digestibility of nutrient from kampung chicken that offered diets with different protein level. The research was conducted for 2 months at Research Station of Faculty of Animal Husbandry, Udayana University Located at Sesetan, Denpasar. This research used 54 kampung chickens ( Gallus domesticus ) with body weight 154 ± 3,295 g. The design used was Completely Randomized Design with three treatments, a rations containing 14.5% protein (R1), rations with 15.5% protein (R2), and rations with 16.5 % protein (R3). This study was conducted with six replications. Rations and water given by adlibitum . Variables of this research are consumption of diets and drinking water, dry matter digestibility, protein digestibility, and digestibility of metabolic energy. The results showed that fed ration iso calory containing 16,5% crude protein (R3) increasing animal feed consumption higher and significant different (P<0,05) compared with R1 and R2. Crude protein digestibility on R3 was higher and significant different (P<0,05) with R1, but not significant different (P>0,05) with R2. The consumption of drinking water on treatments R2 and R3 so higher (P<0,05) compared than R1. On dry matter and metabolism energy digestibility, fed all ration (R1, R2, and R3) were not significant different (P>0,05). It can be concluded that kampung chicken rations given iso energy with level protein 16.5% (R3) can increase consumption ration, consumption of water and protein digesbility. Key words: Kampung chickens, Nutrient Digestibility, Diferent of Level Protein